2011
DOI: 10.1021/nl201206d
|View full text |Cite
|
Sign up to set email alerts
|

Power Factor Enhancement by Modulation Doping in Bulk Nanocomposites

Abstract: We introduce the concept of modulation doping in three-dimensional nanostructured bulk materials to increase the thermoelectric figure of merit. Modulation-doped samples are made of two types of nanograins (a two-phase composite), where dopants are incorporated only into one type. By band engineering, charge carriers could be separated from their parent grains and moved into undoped grains, which would result in enhanced mobility of the carriers in comparison to uniform doping due to a reduction of ionized imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
346
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 481 publications
(358 citation statements)
references
References 35 publications
9
346
3
Order By: Relevance
“…Note that a relatively small change in the Seebeck coefficient between direct doping and modulation doping was also observed experimentally in Ref. [2]. As a result of the superior conductivity, the thermoelectric power factor shown in Fig.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Note that a relatively small change in the Seebeck coefficient between direct doping and modulation doping was also observed experimentally in Ref. [2]. As a result of the superior conductivity, the thermoelectric power factor shown in Fig.…”
Section: Resultssupporting
confidence: 77%
“…In an earlier work we compared the phonon-limited to the phonon plus IIS thermoelectric power factor in Si nanowires (NWs) and demonstrated that both the power factor and ZT could be more than a factor of ~3x lower in the presence of IIS [1]. Thus, modulation doping has been suggested as a possible way to achieve the required high carrier densities, but without the detrimental effects of the ionized dopants in the channel [2]. Indeed, several experimental works indicated that thermoelectric performance modulation over orders of magnitude can be achieved using modulation doping techniques, but in all cases the improvement was only modest [2,3,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Potential ways to improve the power factor are through increasing the Seebeck coefficient (S) via band modification 4 or engineering 5 , energy barrier filtering [6][7][8] , additional carrier pocket 9 , and resonant states 10 , or enhancing the mobility such as modulation doping 11 . Among these possibilities, resonant states and additional carrier pockets have led to net increased ZT values via the power factor enhancements 9,10 .…”
Section: Broader Contextmentioning
confidence: 99%
“…Many efforts have been made to further increase the ZT of Bi 2 Te 3 or its alloys in nanocomposites, 7-10 superlattices, [11][12][13] and bulk materials. [14][15][16][17][18] Although high ZT values were achieved in superlattice structures, bulks with improved ZT are ideal for large-scale energy-conversion applications due to their high efficiency of heat transfer and low cost. Enhancing ZT in Bi 2 Te 3 bulk materials by several possible methods has been reported, such as the use of a nanocomposite approach 7,19 and melt spinning.…”
mentioning
confidence: 99%